Bioerosion on late Quaternary planktonic Foraminifera related to paleoproductivity in the western South Atlantic - Frozza, Cristiane Fraga; Pivel, Maria Alejandra G; Suárez-Ibarra, Jaime Yesid; Ritter, Matias do Nascimento; Coimbra, João Carlos (PANGAEA, 2020)
These datasets include the relative abundances of planktonic foraminifera, relative abundances of drilled specimens, stable isotope data and age model results of sediment core SAT-048A.
Keywords: Bioerosion; boring hole; drilled; ichnofossil; Paleoceanography; paleoecology; paleoproductivity; predation